Hawaiian Monk Seal ( Neomonachus schauinslandi ) Marine Debris Entanglement Risk Varies With Size Class and Sex - Jason D. Baker; Thea C. Johanos; Hope Ronco; Tracy A. Mercer; Brenda L. Becker (Marine Mammal Science, 2026)

Sighting patterns reveal unobserved pupping events to revise reproductive rate estimates for Hawaiian monk seals in the main Hawaiian Islands - Stacie J. Robinson; Albert L. Harting; Tracy Mercer; Thea C. Johanos; Jason D. Baker; Charles L. Littnan (Marine Mammal Science, 2021)
We used sighting reports, including decades of citizen‐reported Hawaiian monk seal ( Neomonachus schauinslandi ) sightings, to describe female breeding biology and reproductive success in the main Hawaiian Islands. We first used this data set to describe the timing of events in the female reproductive cycle. We then conducted an expert review of patterns in sighting histories to detect unobserved pupping events. Finally, we estimated the age‐specific reproductive curve for female monk seals in the main Hawaiian Islands. Charting reproductive cycles showed indications of the robust condition of female monk seals in the main Hawaiian Islands; they nursed pups 12% longer than their counterparts in the Northwestern Hawaiian Islands and regained condition to molt more quickly after weaning a pup. By examining sighting histories, we were able to infer 25 unobserved pupping events that had previously gone uncounted. We accounted for additional uncertainty with a randomization procedure. After accounting for unobserved pupping events, the age‐specific reproductive rate of main Hawaiian Islands monk seals exceeded 0.70 for prime aged females (8–18 years). This is the highest reproductive rate reported for any of the Hawaiian monk seal breeding sites, illustrating the important role of the main Hawaiian Islands population in Hawaiian monk seal recovery.

Population‐level impacts of natural and anthropogenic causes‐of‐death for Hawaiian monk seals in the main Hawaiian Islands - Albert L. Harting; Michelle M. Barbieri; Jason D. Baker; Tracy A. Mercer; Thea C. Johanos; Stacie J. Robinson; Charles L. Littnan; Katie M. Colegrove; Dave S. Rotstein (Marine Mammal Science, 2021)
Identifying, assessing, and ranking the impact of individual threats is fundamental to the conservation and recovery of rare and endangered species. In this analysis, we quantify not only the frequency of specific causes‐of‐death (CODs) among Main Hawaiian Island (MHI) monk seals, but also assess the impact of individual CODs on the intrinsic growth rate, λ, of the MHI population. We used gross necropsy results, histopathology, and other evidence to assign probabilities of 11 COD types to each mortality and then used Monte Carlo sampling to evaluate the influence of each COD on λ. By right censoring realizations involving specific CODs, we were able to estimate λ (and its associated uncertainty) when CODs were selectively removed from influencing survival. Applying the analysis to all known and inferred deaths believed to have occurred 2004–2019, the CODs with the largest influence on λ were anthropogenic trauma, anthropogenic drowning, and protozoal disease. In aggregate, anthropogenic CODs had a larger effect on the growth rate than either natural or disease CODs. Possible bias associated with differential carcass detection, recovery, and COD classification are discussed.